2008
DOI: 10.1111/j.1651-2227.2008.00902.x
|View full text |Cite
|
Sign up to set email alerts
|

Human toxocariasis: a report of nine cases

Abstract: Aim: Human toxocariasis is caused by infection with the larval stage of nematode parasites of dogs and cats, Toxocara canis or Toxocara cati. These helminths are not able to complete their life cycle in undefinitive hosts and so undergo aberrant migrations in the tissues causing a wide spectrum of signs and symptoms. Eosinophilia is often severe and sometimes represents the only sign of infection, except in ocular and neurological forms. Results: Fever and hepatomegaly were the most common clinical findings. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 8 publications
0
10
0
4
Order By: Relevance
“…For instance, some cases with longer incubation period may have been directly attended in the primary care setting given the fact that the link between symptoms and travel had become less obvious. Also our observations are not transposable as such to the features observed in autochthonous toxocariasis sporadically seen in Belgium or elsewhere, mainly in children [ 22 ]. Other limitations could be related to the restrictive case definition that may have missed several true cases without eosinophilia (as sometimes observed in milder cases of “covert/common” toxocariasis) or with negative Toxocara serology (during the serological window period or because sensitivity does not reach 100%, in particular in low burden infection such as ocular toxocariasis [ 2 ]).…”
Section: Discussionmentioning
confidence: 50%
“…For instance, some cases with longer incubation period may have been directly attended in the primary care setting given the fact that the link between symptoms and travel had become less obvious. Also our observations are not transposable as such to the features observed in autochthonous toxocariasis sporadically seen in Belgium or elsewhere, mainly in children [ 22 ]. Other limitations could be related to the restrictive case definition that may have missed several true cases without eosinophilia (as sometimes observed in milder cases of “covert/common” toxocariasis) or with negative Toxocara serology (during the serological window period or because sensitivity does not reach 100%, in particular in low burden infection such as ocular toxocariasis [ 2 ]).…”
Section: Discussionmentioning
confidence: 50%
“…Este parasito é responsável pela zoonose conhecida como Toxocariase, que ocorre pela ingestão acidental de ovos embrionados. Os sinais clínicos da enfermidade decorrem da reação inflamatória ocasionada pela migração do parasito, de acordo com o órgão afetado, sendo classificada em: Larva migrans visceral (LMV), Larva migrans ocular (LMO), oculta ou atípica e assintomática (HARALAMBIDOU et al, 2005;SAPORITO et al, 2008;ABOUGRAIN et al, 2009). Nos animais, os filhotes são mais acometidos, o que pode ser explicado pelo fato da transmissão lactogênica e transplacentária serem as principais fontes de infecção, e também pelo sistema imunológico imaturo durante essa faixa etária (BOWMAN et al, 2003).…”
Section: Resultsunclassified
“…Alcântara-Neves et al (2014) found strong positive association between helminthiasis and both total IgE and eosinophilia. Saporito et al (2008) and Bahnea et al (2008) reported that eosinophilia and high IgE level in asthmatic patients suggested toxocariasis. The present study, found significant negative relation between toxocariasis seropositivity and skin prick test.…”
Section: Discussionmentioning
confidence: 99%